Two-year outcomes after selective early treatment of patent ductus arteriosus with ibuprofen in preterm babies: follow-up of Baby-OSCAR–a randomised controlled trialResearch in context - Samir Gupta; Heather O'Connor; Edmund Juszczak; Nimish V. Subhedar; Ursula Bowler; Charlotte Clarke; David Field; Elizabeth Hutchison; Wilf Kelsall; Justine Pepperell; Tracy Roberts; Sunil Sinha; et al. (EClinicalMedicine)
Summary: Background: Children born extremely preterm are at increased risk of developmental problems and respiratory morbidity due to patent ductus arteriosus (PDA). The objective of this study was to evaluate whether early treatment of a PDA ≥1.5 mm with ibuprofen improved neurodevelopmental and respiratory outcomes at 24 months of age, corrected for prematurity. Methods: Baby-OSCAR was a UK multi-center placebo-controlled masked randomized clinical trial in infants born 23+0–28+6 weeks' gestation. The main long-term outcome was survival without moderate or severe neurodevelopmental impairment at 24 months’ corrected age, assessed using parent report primarily or classified by blinded end-point review committee where parent-reported data were not available. Other secondary outcomes included survival without respiratory morbidity and duration of oxygen supplementation. (ISRCTN Registry number ISRCTN84264977). Findings: From July 2015 through December 2020, 653 infants underwent randomization. At 24 months’ corrected age, outcome data were available for 537 children: 263 in the ibuprofen group and 274 in the placebo group. Survival without moderate to severe neurodevelopmental impairment in the ibuprofen and placebo groups was 131/248 (53.0%) and 134/259 (51.9%) respectively; adjusted risk ratio 1.01 (95% confidence interval [CI] 0.86–1.18); p = 0.901. Survival without respiratory morbidity was 66/220 (30%) and 74/225 (32.9%) respectively; adjusted risk ratio 0.89 (95% CI 0.68–1.18). Median duration of oxygen supplementation from randomization was 76.0 and 78.0 days, respectively; adjusted median difference −1.5 (−13.8 to 10.9). Interpretation: We found no evidence of an improvement in neurodevelopmental and respiratory outcomes at 24 months’ corrected age, after selective early treatment of a PDA ≥1.5 mm with ibuprofen in children born extremely preterm. Funding: This study was funded by the National Institute for Health Research (NIHR) Health Technology Assessment Programme (11/92/15).